Back Cover: Diversified Structural Basis of a Conserved Molecular Mechanism for pH‐Dependent Dimerization in Spider Silk N‐Terminal Domains (ChemBioChem 12/2015). Issue 12 (17th August 2015) - Otikovs, Martins; Chen, Gefei; Nordling, Kerstin; Landreh, Michael; Meng, Qing; Jörnvall, Hans; Kronqvist, Nina; Rising, Anna; Johansson, Jan; Jaudzems, Kristaps
<x xml:space="preserve">Abstract</x> The back cover picture shows the dimerization of the spider silk N‐terminal domain as part of silk fiber formation. On p. 1720 ff., J. Johansson, K. Jaudzems and co‐workers show that the dimerization involves a stepwise uptake of three protons by three glutamic acids. This mechanism is conserved among different spider species and silk types despite sequence variations.